Linking the nitrous oxide production and mitigation with the microbial community in wastewater treatment: A review. (September 2019) - Ren, Yi; Ngo, Huu Hao; Guo, Wenshan; Ni, Bing-Jie; Liu, Yiwen
Abstract: Nitrous oxide (N2 O) is largely produced during wastewater treatment. However, there is a lack of review on linking N2 O production and mitigation with microbial communities in wastewater treatment. In this study, various microbial communities contributing to N2 O turnovers are reviewed according to their functions in nitrogen cycle, including ammonia oxidizing bacteria and archaea, comammox bacteria, autotrophic denitrifying bacteria, heterotrophic denitrifying bacteria and non-denitrifying N2 O reducers. Their metabolic pathways and enzymatic reactions of N2 O production are demonstrated, including nitrifier denitrification, nitritation, archaeal N2 O production and denitrification pathways. The N2 O emission factor of the nitrifier denitrification pathway is generally higher than nitritation pathway, and that of denitrifying bacteria depends on species and electron acceptors. The mitigation strategies are developed according to the dominating microbial communities. Overall, this review illustrates a comprehensive characteristic of N2 O production by microbial communities in wastewater treatment, which could contribute to the development of effective N2 O mitigation strategies. Highlights: The relationship between microbial communities and N2 O turnover in WWTP is reviewed. The metabolic pathways and enzymatic reactions of N2 O production are demonstrated. The emission factors of various N2 O production communities are revealed. N2 O mitigation strategies are developed as per dominating microbial communities.